Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1021/ie060955b
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Carbon Nanotube Synthesis via Fluidized-Bed Chemical Vapor Deposition

Abstract: Carbon nanotubes (CNTs) are crystalline, tubular, carbon structures with extraordinary mechanical, chemical, optical, and electrical properties. These unique properties make CNTs potentially valuable in a wide range of end-use applications. Currently, research into nanotubes and their applications is hampered by the lack of a suitable technique for manufacturing them in large quantities, which we define here as 10 000 tons per plant per year. Consequently, research into large-scale manufacturing techniques is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
152
0
6

Year Published

2011
2011
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 274 publications
(165 citation statements)
references
References 150 publications
1
152
0
6
Order By: Relevance
“…Carbon saturation in the metal occurs either by reaching the carbon solubility limit in the metal at a given temperature or by lowering the solubility limit via temperature decrease (Moisala et al, 2003). Supersaturation of the saturated solution then results in precipitation of solid carbon from the metal surface (Moisala et al, 2003;See and Harris, 2007). In summary, the mechanism of the catalytic growth of CNT or carbon nanofibre (CNF) is generally accepted as consisting of three steps (de Jong and Geus, 2000): The first step is the decomposition of carbon containing gases on the metal surface, with carbon atoms deposited on the surface.…”
Section: Growth Mechanismsmentioning
confidence: 99%
“…Carbon saturation in the metal occurs either by reaching the carbon solubility limit in the metal at a given temperature or by lowering the solubility limit via temperature decrease (Moisala et al, 2003). Supersaturation of the saturated solution then results in precipitation of solid carbon from the metal surface (Moisala et al, 2003;See and Harris, 2007). In summary, the mechanism of the catalytic growth of CNT or carbon nanofibre (CNF) is generally accepted as consisting of three steps (de Jong and Geus, 2000): The first step is the decomposition of carbon containing gases on the metal surface, with carbon atoms deposited on the surface.…”
Section: Growth Mechanismsmentioning
confidence: 99%
“…To generate carbon nanomaterials carbon bearing gases are needed at an elevated temperature environment. Such gases can be generated by high temperature pyrolysis and/or combustion of hydrocarbon-based feedstocks 12 . In prior work, it was found that carbon bearing gases can be provided from other types of solid waste fuels, such as plastics 13 and biomass 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Many other articles have reviewed the growth of singleand multi-walled carbon nanotubes, using either arc discharge, laser ablation, or catalytic CVD techniques [4][5][6][7][8][9][10][11][12][13][14][15][16].…”
mentioning
confidence: 99%